Agricultural financing risk and ib agricultural financing: A long relationship - Alan Nur, Muhammad; Honesty Nur Firdaus; Armanto, Andre; Herianingrum, Sri (JIFA (Journal of Islamic Finance and Accounting), 2022)
Indonesia is destined to be an agrarian country because of its location on the equator, unfortunately not all farmers are able to access capital for their agricultural businesses while the contribution of the agricultural sector to employment is very high. It is also important to consider that Indonesia is also a country with the largest Muslim population in the world, so there should be a financing scheme in the agricultural sector that is in accordance with sharia compliance. Therefore, Islamic banking should be present to provide capital to farmers who need agricultural financing without violating sharia provisions. Identifying variables that affect Islamic bank financing in the agricultural sector in the long run is the aim of this study so that our findings can be one of the considerations for policy makers for future policies. To reveal the purpose of our research, we consider the factors affecting the agricultural financing of Islamic banks which consist of the risk of agricultural financing, farmer welfare, inflation and economic growth with observations for a decade from 2012 to 2021 on a quarterly basis. By using ARDL estimation, our findings find that in the long run relationship the welfare of farmers has no effect, while the other remaining variables have a significant effect. This study offers valuable implications indicating that the presence of Islamic banking can be considered as a viable financial solution within the agricultural sector.